Associations of maternal trait anger expression and lifetime traumatic and non-traumatic experiences with preterm birth - Cowell, Whitney (Matern Child Health J, 2020)
OBJECTIVES: Most studies examining psychosocial factors contributing to preterm birth (PTB) have focused on negative life events. Studies examining the influence of negative emotion, in particular maternal anger, remain sparse. We examined associations of maternal trait anger expression and lifetime traumatic and non-traumatic experiences with the risk of PTB. METHODS: Mother-newborn pairs were enrolled in the PRogramming of Intergenerational Stress Mechanisms pregnancy cohort based in Boston and New York City. Women completed the State-Trait Anger Expression Inventory-2 (STAXI-2), Life Stressor Checklist-Revised (LSC-R), and Childhood Trauma Questionnaire (CTQ) in pregnancy. We used modified Poisson regression to estimate the relative risk (RR) of PTB 1) in relation to continuous STAXI-2 trait Anger Expression-In (AX-I) and trait Anger Expression-Out (AX-O) subscales, 2) in relation to continuous LSC-R scores, and 3) between women who did versus did not experience childhood sexual, emotional, and/or physical abuse in six separate models. We also examined interactions between maternal anger expression and lifetime stress/childhood trauma. RESULTS: Younger, single, minority women had higher outward anger expression and inward anger suppression. Trait AX-I and AX-O scores were higher among women who experienced abuse in childhood and who had higher lifetime stress. Maternal lifetime stress, outward anger expression, and inward anger suppression were associated with an increased risk of PTB in separate models; however, stress, trauma and anger did not interact to further increase the risk of PTB. CONCLUSIONS: Higher anger expression and higher lifetime stress experiences were associated with an increased risk of PTB among a racially and ethnically diverse sample of pregnant women. SIGNIFICANCE: Preterm birth (PTB) is a leading cause of infant mortality and morbidity and has consequences for long-term health. Accumulating evidence supports that psychosocial stress and stress correlates (e.g., depression) contribute to the pathophysiology underlying adverse obstetrical outcomes, including PTB. Few studies have examined the influence of negative emotions, including anger expression, on adverse birth outcomes. In this study, higher outward anger expression and inward anger suppression were associated with an increased risk of PTB even after adjusting for potential confounders. Lifetime stress was also positively associated with PTB, but childhood abuse subscales were not.